Increasing household preparedness for earthquakes : understanding how individuals make meaning of earthquake information and how this relates to preparedness : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Wellington, New Zealand - Becker, Julia Susan (Massey University, 2012)
New Zealand’s susceptibility to experiencing damaging earthquakes makes managing the associated risk a societal imperative. A prominent component of earthquake risk management is fostering household earthquake preparedness. This involves encouraging people to acquire survival items (e.g. food, water, torches, and other essential items), implement mitigation measures (e.g. retrofit buildings), make emergency plans, learn survival skills and engage in socially-based preparedness activities. Despite considerable effort and expenditure incurred by emergency management to encourage such activities, levels of overall preparedness remain low in New Zealand. This identifies a need for more effective earthquake education programmes. To develop more effective programmes, it is important to understand how people make sense of hazards and make decisions about how to manage the associated risk. One particular gap in current understanding relates to how individuals render earthquake hazard and preparedness information meaningful and how this influences actual preparedness. In particular, questions remain about how individual, community and societal factors interact to influence how people interpret risk and decide whether to prepare or not. This thesis explores the earthquake information meaning-making and preparedness processes. A series of qualitative interviews using grounded theory methodology was undertaken in 2008 with household residents in three New Zealand locations at risk of earthquakes. The interviews explored personal, community and societal influences on how people interpret and impose meaning on earthquake information and how the outcome of this process relates to undertaking actual preparedness actions. Three main types of information were identified: passive; interactive; and experiential information. Each type of information makes unique contributions to the interpretation and preparedness process. Passive information has a more restricted effect, and interactive and experiential information a wider-ranging effect. People utilise all these types of information when interpreting and making meaning of hazard and preparedness issues. Consequently, future earthquake education programmes should accommodate passive, interactive and experiential information in their design and implementation. In making meaning of information, and making decisions about whether to prepare or not, a number of aspects were found to be important to the overall process including: raising awareness and knowledge of earthquakes and preparedness; understanding earthquake consequences; stimulating thought and discussion; developing skills; information seeking; salient beliefs; emotions and feelings; societal influences; intentions to prepare; and resource issues. Key societal influences on meaning-making and preparedness include: community (community participation, sense of community); leadership; responsibility (responsibility for preparing, responsibility for others); social norms; trust; and societal requirements. Earthquake education programmes also need to take such factors into account in their design.
Keywords: Earthquakes; Risk management; Emergency management; Preparedness; Earthquake information; Emergency planning; Earthquake education